Ultra-short multi soliton generation for application in long distance communication - Amiri, I. S. (2013)
Generation of picometer optical soliton pulses is investigated using a nonlinear PANDA ring resonator system connecting to an add/drop filter system. The objectives of the research are to employ systems of microring resonator (MRR) to generate binary signals to be carried out along fiber optic communication. Effective parameters such as refractive indices of a silicon waveguide, coupling coefficients (? ), coupling loss, radius of the ring (R) and the input power can be selected properly to operate the nonlinear behavior. The input Gaussian laser pulses with power of 600 mW are inserted into the system. The central wavelength of the input power has been selected to ?0=1.55 µm where the nonlinear refractive index of the medium is n2=2.6×10-17 m 2 W-1 . Therefore binary signals generated by the add/drop filter system can be converted to secure codes where the decoding process of the transmitted codes can be obtained at the final step. Here, multi soliton pulses with full width at half maximum (FWHM) of 325 could be generated, converted to secure codes and finally detected over 70 km optical fiber communication link.